The impact of aging on spreading depolarization in the intact and ischemic rat brain - Menyhárt Ákos; Farkas Eszter (2017)
Background: Aging emerges as a major independent risk factor for the incidence and prevalence of ischemic stroke and predicts poor patient outcomes. In our aging population, much of the primary injury in the acute phase of ischemic stroke may prove irreversible, yet the management of secondary pathophysiological processes is of fundamental importance to improve the prospect of successful recovery. Spontaneously occurring recurrent spreading depolarizations (SDs) were recognized as contributors of the expansion of cerebral tissue damage following subarachnoid hemorrhage, stroke or traumatic brain injury. Hypothesis: Since the aged brain is more susceptible to ischemia- and SD-related injury, we hypothesized, that (1) the evolution of SDs and the related hemodynamic responses could be altered by aging and (2) the SD associated metabolic changes, such as tissue acidosis should also be graver in the aged ischemic brain. Aims: We set out to determine; (1) the impact of age on the evolution of SD and the kinetics of the associated changes in local CBF in the intact and ischemic rat brain, (2) the impact of age on the SD related tissue pH changes in the intact and ischemic rat brain, and (3) the association between the SD-related pH transients and SD-related CBF responses. Methods: Open or closed cranial windows were mounted on the parietal bone of halothane or isoflurane-anesthetized young (2-months-, n=33) and old (18-20-month-old, n=18, and 2-year-old, n= 26) Sprague Dawley or Wistar rats. Mean arterial blood pressure and arterial blood gases were monitored via a femoral artery catheter. Transient incomplete global forebrain ischemia was achieved by the bilateral occlusion of the common carotid arteries (2VO). SDs were elicited by the topical application of KCl. The evolution of SDs and –the associated local CBF changes were acquired by the measurement of DC potential and laser-Doppler flowmetry. SD-related variations in extracellular pH were acquired with pH-sensitive microelectrodes inserted into the cortex. SD-coupled intracellular pH- and perfusion changes were monitored relying on the fluorescence intensity of a pH indicator dye (Neutral Red), and laser speckle contrast analysis, respectively. Results: Ischemia elongated the duration of the SD-related negative DC shift (66.2±22.8 vs. 21.4±4.1 s, Young 2VO vs. Young control), which was augmented further by age as seen in the Old 2VO group (95.8±46.2 s). Six types of SD-coupled CBF responses were identified, ranging from dominating hyperemia to prolonged cortical spreading ischemia with intermediate forms. Spreading ischemia evolved only in the aged ischemic group (4 of the 6 animals). Quantitative analysis of the duration of early hypoperfusion indicated that this first element of the CBF response to SD was elongated during ischemia (36.8±17.5 vs. 7.9±6.8 sec, Young 2VO vs. Young control) and became drastically longer in the Old 2VO group (1344±1047 sec), due to the prevalence of spreading ischemia. Acid accumulation with SDs propagating across the ischemic cortex was considerably increased with respect to the intact and reperfused condition (e.g. relative amplitude of acidosis: pH 0.43±0.15 vs. 0.36±0.07 vs. 0.31±0.09, ischemia vs. intact vs. reperfused). Tissue acidosis with SD was additive to ischemia-induced acidosis thereby raising acid load to potentially cytotoxic levels (level of acidosis: pH 6.48±0.16 vs. 6.93±0.09, with SD under ischemia vs. ischemia alone prior to SD onset). In addition, tissue pH remained acidic for at least 10 min after the passage of an SD (pH 7.09±0.09 vs. 7.29±0.16, 12 min after SD vs. time control ischemia without SD), which was further deepened in the aged brain (pH 6.94±0.08 vs. 7.09±0.09, old vs. young). Discussion: While ischemia clearly compromised the kinetics of SDs and the associated CBF response, age exerted an additional shift to more injurious CBF response types including spreading ischemia. We propose that structural and functional alteration of the cerebro-microvascular system with aging serves as a potential basis for compromised vascular reactivity. The prospect of successful recovery after stroke strongly depends on the metabolic statement of the affected tissue. Marked tissue acidosis correlates with the extent of brain injury, and has been traditionally considered as a damaging component of cerebral ischemia. In conclusion, SDs are suggested to extend ischemic lesions by increasing acid accumulation in the ischemic penumbra to toxic levels characteristic of the ischemic core. Repeated SDs typically evolving in the ischemic cortex are expected to maintain low pH, which decreases the threshold of acid-induced cell death. Finally, the aged brain may be at higher risk for SD-related injury, because the recovery of tissue pH after SD is hampered.
Disszertacio
Keywords: elméleti orvostudományok